2023
DOI: 10.21037/qims-22-1057
|View full text |Cite
|
Sign up to set email alerts
|

The optimal tibial tunnel placement to maximize the graft bending angle in the transtibial posterior cruciate ligament reconstruction: a quantitative assessment in three-dimensional computed tomography model

Abstract: Background The graft bending angle created by the graft and the tibial tunnel has inevitably occurred during the transtibial posterior cruciate ligament (PCL) reconstruction. However, few studies quantitively analyzed this angle. This study aimed to (I) explore the optimal tibial tunnel placement to maximize the graft bending angle in the PCL reconstruction; (II) reveal the effect of the tibial tunnel placement on the graft bending angle. Methods This was an in-vitro su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Therefore, the outcomes need to be validated by future clinical or cadaveric studies. Previous studies have demonstrated that 3D knee joint models can be used for precise quantitative analysis and exhibit excellent measurement accuracy and reliability [ 22 ]. Therefore, the results of this study can facilitate surgeons in better preoperative planning and intraoperative estimation of TTL.…”
Section: Limitationsmentioning
confidence: 99%
“…Therefore, the outcomes need to be validated by future clinical or cadaveric studies. Previous studies have demonstrated that 3D knee joint models can be used for precise quantitative analysis and exhibit excellent measurement accuracy and reliability [ 22 ]. Therefore, the results of this study can facilitate surgeons in better preoperative planning and intraoperative estimation of TTL.…”
Section: Limitationsmentioning
confidence: 99%
“…Although the posterior cruciate ligament reconstruction (PCLR) technique has evolved considerably over recent decades [1,14,15], there is still no consensus regarding the optimal surgical approach for PCLR [6,11], including whether to perform single-bundle or doublebundle reconstruction [20], whether to perform transtibial or tibial inlays and the positioning of the tunnel. Currently, there are many possible reasons for the failure of PCLR surgery [21], one of which is incorrect bone tunnel placement [24], particularly positioning of the tibial bone tunnel, which is considered to be very important in PCLR [8,18].…”
Section: Introductionmentioning
confidence: 99%